Photochemical degradation of dissolved organic matter reduces the availability of phosphorus for aquatic primary producers - Porcal, Petr; Kopáček, Jiří (Chemosphere, 2018)
In situ experiments were done to determine the effects of the photochemical degradation of dissolved organic matter (DOM) and subsequent formation of particulate matter on dissolved phosphorus (P) concentrations in surface waters. Filtered (1.2 or 0.4 μm) headwaters (DOM of 8.1-26 mg L-1; P of 22-43 μg L-1) were exposed to solar radiation in quartz bottles located 5 cm below the water surface for 7-10 days. Dark controls were wrapped in aluminum foil. After incubation, particulate organic carbon (POC) and particulate phosphorus (PP) were determined in both the filtrate and newly formed particles. The results revealed increasing concentrations of PP and POC in exposed samples with increasing exposure time (cumulative irradiation energy). At the end of experiments, PP concentrations were from 5 to 20 μg L-1 in the exposed samples. Based on an enumeration of bacteria in the samples, we estimated the contribution of biotic and abiotic processes to the PP production. The abiotic PP formation ranged from 56 to 83% and 50-95% of the total PP in the exposed and control samples, respectively. The remainder was assumed to be bacterial P uptake. Despite the overlapping intervals, biotic and abiotic PP productions were usually higher in exposed samples than in controls. The PP and POC production was affected by the properties of DOM, such as its humic content and freshness index. We hypothesize that the observed immobilization of dissolved P in bacteria and on photochemically-formed particles can contribute to a P limitation of primary production in headwater environments that receive waters rich in soil DOM.
Keywords: fotochemie; fosfor; Particulate Matter; Photochemistry; Aluminum; pevné částice; Phosphorus; Iron; Dissolved organic matter